Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1080/17441692.2012.662991
|View full text |Cite
|
Sign up to set email alerts
|

Occupational safety and HIV risk among female sex workers in China: A mixed-methods analysis of sex-work harms and mommies

Abstract: Female sex workers (FSWs) in China are exposed to multiple work-related harms that increase HIV vulnerability. Using mixed-methods, we explored the social-ecological aspects of sexual risk among 348 FSWs in Beijing. Sex-work harms were assessed by property stolen, being underpaid or not paid at all, verbal and sexual abuse, forced drinking; and forced sex more than once. The majority (90%) reported at least one type of harm, 38% received harm protection from ‘mommies’ (i.e., managers) and 32% reported unprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Physical access to relevant services and supplies also may reflect important features of venue-level social relations whereby SWs, managers and peers collectively support and facilitate condom use 19 30. Qualitative studies on sex work policies and management in India, China and brothels in Nevada, also have reported that managers may represent important ‘nodes’ for sexually transmitted infection (STI) information, and provide protection from violence, contributing to increased condom use 23 35 36…”
Section: Discussionmentioning
confidence: 99%
“…Physical access to relevant services and supplies also may reflect important features of venue-level social relations whereby SWs, managers and peers collectively support and facilitate condom use 19 30. Qualitative studies on sex work policies and management in India, China and brothels in Nevada, also have reported that managers may represent important ‘nodes’ for sexually transmitted infection (STI) information, and provide protection from violence, contributing to increased condom use 23 35 36…”
Section: Discussionmentioning
confidence: 99%
“…Within criminalised environments, physical and sexual violence in the workplace, whether by clients, police, managers, pimps, or predators posing as clients, are among the most ubiquitous and influential determinants of HIV acquisition and transmission risk among FSWs, linked to inconsistent condom use, client condom refusal, condom use failure and breakage,22, 24, 26, 28, 33, 43, 46, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57 and HIV infection. 5, 33, 58, 59, 60, 61, 62 In addition to police abuse as a human rights violation, law enforcement strategies and local policing of sex work, including arrests and incarceration, 26, 38, 61, 63, 64, 65 raids, 64 displacement, 24 and confiscation of condoms or syringes, 64, 66 are key barriers to HIV prevention efforts among FSWs worldwide, which reduces or eliminates the ability to negotiate male condom use 24, 51, 61, 63, 64, 66 and increases HIV prevalence and incidence.…”
Section: Structural Determinants Of Hivmentioning
confidence: 99%
“…The authors of these studies examined how supportive venue-based policies 30, 32, 76, 77, 78, 79, 80, 81 or managerial practices (eg, client sign-in, safety mechanisms, or removal of violent clients) 48, 69, 76, 77, 80, 81, 82, 83, 84, 85 and physical features (eg, types or layout of venues) of sex work establishments are associated with increased condom use, often through synergistic effects with other social features of increased peer or sex worker support 32, 52, 53, 69, 72, 76, 79, 81, 83, 85, 86, 87, 88, 89, 90. Work environments for FSWs are shaped by economic features (eg, economic pressures, client financial incentives for non-condom use, refusal of payment, and bribes or fines by state agents [eg, police] to avoid arrest) resulting from macrostructural forces of poverty, laws, and access to resources and are associated with non-condom use27, 28, 29, 30, 40, 41, 48, 64, 70, 83, 84, 87, 91, 92, 93 and HIV infection among FSWs. 36, 65, 75, 94 Conversely, higher income and absence of economic dependence among FSWs mitigate HIV risks, including increased condom use 40, 48, 80, 86, 87 and lower HIV prevalence.…”
Section: Structural Determinants Of Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical and sexual abuse perpetrated by clients,and those posing as clients, is common, and often occurs during condom negotiation. 25,34-36,40,45,48,50,53,70-72 Client-perpetrated physical and sexual violence, including forced anal sex, 73 is associated with STI/HIV risk behavior 39,45,70,72 and infection. 39,45,73,74 Abuse is fueled in part by recognition of sex workers’ barriers to seeking justice, which enables perpetration of physical and sexual violence with impunity.…”
Section: Introductionmentioning
confidence: 99%